MAGIC: conoscere i mari italiani e individuarne i geo-rischi - Bosman, Alessandro; Casalbore, Daniele; Ridente, Domenico; Montanaro, Cristian; Chiocci, Francesco L. (GEOmedia, 2010)
MAGIC project: Marine Geohazard along the Italian Coasts MAGIC Project is funded by the Italian Civil Protection Department (DPC) to produce a bathymetric database as reference for compiling maps (1:50.000) of marine geo-hazard. During its 5-year life span (2007-2012), MAGIC will allow the acquisition of high-resolution multibeam bathymetry along the Italian continental margins and will involve the entire Italian scientific community currently active in the field of Marine Geology. More than 73.000 nautical miles of multibeam data will be analyzed, allowing comparison of geological features produced by sedimentary and tectonic processes (i.e. volcanic events, submarine landslide, active faulting). The main objective of MAGIC is to furnish the DPC accurate depiction of superficial geology and relatedgeo-hazard on the most sensitive and hazard-prone areas.